Glass ceramic, manufacturing method thereof, structural member and electronic equipment

By adjusting the content of each component in the microcrystalline glass and carrying out specific heat treatment and ion exchange treatment, the problem of unsatisfactory mechanical properties of the existing microcrystalline glass is solved, high impact resistance and fracture resistance are achieved, and its mechanical properties are improved.

CN119898960APending Publication Date: 2025-04-29BEIJING XIAOMI MOBILE SOFTWARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311402064.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The mechanical properties of existing microcrystalline glasses are not ideal, especially their impact resistance and fracture resistance.

Method used

By adjusting the content of each component in the microcrystalline glass, including SiO2, Al2O3, Li2O+Na2O+K2O, ZrO2, P2O5 and Y2O3, it is ensured that the mass proportion of the microcrystalline phase in the microcrystalline glass accounts for more than 90%, and its mechanical properties are improved through specific heat treatment and ion exchange treatment.

Benefits of technology

The good impact resistance and fracture resistance of microcrystalline glass are achieved, the fracture toughness can be greater than 1.0MPa·m1/2, and the Vickers hardness is greater than 860HV50/10.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898960A_ABST
    Figure CN119898960A_ABST
Patent Text Reader

Abstract

The invention provides microcrystalline glass, a manufacturing method of the microcrystalline glass, a structural member and electronic equipment, and the microcrystalline glass comprises the following components in percentage by mass: 60-71 wt% of SiO2; al2O3: 5 wt% to 13 wt%; li2O + Na2O + K2O: 9 wt% to 18 wt%; zrO2: 1.5 wt% to 6.5 wt%; 1.5 wt% to 5.5 wt% of P2O5; and Y2O3: 0.1 wt% to 1.4 wt%. By adjusting the content of each component in the glass ceramic, the obtained glass ceramic has good impact resistance and fracture resistance, and the fracture toughness can be greater than 1.0 MPa.m < 1 / 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of material technology, and in particular to a glass-ceramic and a manufacturing method thereof, a structural component and an electronic device. Background Art

[0002] Glass-ceramics is often used as a substitute for glass or ceramics because it has both the basic properties of glass and the polycrystalline characteristics of ceramics, and its performance indicators are better than similar glasses and ceramics. At present, the mechanical properties of glass-ceramics are still not ideal. Summary of the invention

[0003] In order to overcome the problems existing in the related art, the present disclosure provides a microcrystalline glass and a manufacturing method thereof, a structural component and an electronic device.

[0004] According to a first aspect of the present disclosure, a glass-ceramic is provided, wherein the components of the glass-ceramic include, by mass percentage:

[0005] SiO2: 60wt%-71wt%; Al2O3: 5wt%-13wt%; Li2O+Na2O+K2O: 9wt%-18wt%; ZrO2: 1.5wt%-6.5wt%; P2O5: 1.5wt%-5.5wt%; Y2O3: 0.1wt%-1.4wt%.

[0006] In some embodiments of the present disclosure, the mass percentage ratio C1=SiO2 / Al2O3 ranges from 4.6 to 14.2.

[0007] In some embodiments of the present disclosure, in the microcrystalline glass, by mass percentage, Li2O: 8wt%-16wt%; Na2O: 0.8wt%-3.0wt%; K2O: 0.2wt%-1.0wt%.

[0008] In some embodiments of the present disclosure, the mass percentage ratio C2=(SiO2+Al2O3) / Li2O ranges from 4.0 to 10.5.

[0009] In some embodiments of the present disclosure, the microcrystalline glass includes a microcrystalline phase, the microcrystalline phase includes a first crystal phase and a second crystal phase, the first crystal phase includes one or more of petalite, β-spodumene, and β-eucryptite, and the second crystal phase includes one or more of lithium disilicate, lithium metasilicate, and zirconium oxide;

[0010] In the unit mass of the microcrystalline glass, the ratio of the mass of the microcrystalline phase to the unit mass is greater than 90%.

[0011] In some embodiments of the present disclosure, in a unit mass of the microcrystalline glass, the mass proportion of the first crystalline phase is 50%-70%; the mass proportion of the second crystalline phase is 30%-45%.

[0012] In some embodiments of the present disclosure, the grains of the microcrystalline phase are spherical, and the size of the grains ranges from 10 nm to 70 nm.

[0013] In some embodiments of the present disclosure, the microcrystalline glass further includes a glass phase, and every two adjacent grains of the microcrystalline phase are interlocked by the glass.

[0014] In some embodiments of the present disclosure, the components of the glass-ceramics include, by mass percentage:

[0015] SiO2: 60wt%-70wt%; Al2O3: 5wt%-12wt%; Li2O+Na2O+K2O: 9wt%-15wt%; ZrO2: 2wt%-5wt%; P2O5: 2wt%-5wt%; Y2O3: 0.1 wt%-1.4wt%; B2O3: 0wt%-5wt%; TiO2: 0wt%-4wt%; MgO: 0wt%-2wt%; ZnO: 0wt%-2wt%; SrO: 0wt%-2wt%; Clarifying agent: 0wt%-2wt%.

[0016] In some embodiments of the present disclosure, the clarifier includes one or more of Sb2O3, SnO2, SnO, and CeO2.

[0017] In some embodiments of the present disclosure, the Vickers hardness of the microcrystalline glass is greater than 860 HV50 / 10; the fracture toughness of the microcrystalline glass is greater than 1.0 MPa·m 1 / 2 .

[0018] According to a second aspect of the present disclosure, a method for manufacturing a glass-ceramic is provided, which is used to manufacture the glass-ceramic provided in the first aspect of the present disclosure, and the method for manufacturing the glass-ceramic comprises:

[0019] Based on the mass percentage of each component, under the first preset condition, each of the components is melted to obtain a glass-ceramic melt;

[0020] Injecting the glass-ceramics melt into a mold at a preset temperature to form a precursor glass ingot;

[0021] Under a second preset condition, annealing the precursor glass ingot to obtain a glass-ceramic ingot;

[0022] Under a third preset condition, the glass-ceramic ingot is heat treated.

[0023] In some embodiments of the present disclosure, the first preset condition includes: a smelting temperature of 1550° C.-1660° C., a smelting time of 5 h-10 h; and / or,

[0024] The preset temperature is 750°C-800°C; and / or,

[0025] The second preset conditions include: annealing temperature of 500° C.-800° C., annealing time of 5 h-12 h; and / or,

[0026] The third preset condition includes: the heat treatment temperature is 600° C.-750° C., and the heat treatment time is 2 h-6 h.

[0027] In some embodiments of the present disclosure, the method for manufacturing the microcrystalline glass further includes:

[0028] The glass-ceramics ingot that has completed the heat treatment is cut, ground and polished in sequence to obtain a glass-ceramics semi-finished product;

[0029] Under a fourth preset condition, the microcrystalline glass semi-finished product is subjected to ion exchange treatment to obtain the microcrystalline glass.

[0030] In some embodiments of the present disclosure, the semi-finished glass-ceramics product is subjected to ion exchange treatment, including:

[0031] Immersing the semi-finished glass-ceramics product in a molten first mixed salt for a first treatment;

[0032] Immersing the semi-finished glass-ceramics product that has undergone the first treatment in a molten second mixed salt for a second treatment;

[0033] Wherein, the first mixed salt and the second mixed salt both include NaNO3 and KNO3.

[0034] In some embodiments of the present disclosure, in the first mixed salt, the mass ratio of NaNO3 to KNO3 is 4:6;

[0035] In the second mixed salt, the mass ratio of NaNO3 to KNO3 is 3:7.

[0036] In some embodiments of the present disclosure, the fourth preset condition corresponding to the first treatment includes: the temperature of the first mixed salt is 450°C-550°C, and the soaking time is 4h-8h;

[0037] The fourth preset condition corresponding to the second treatment includes: the temperature of the second mixed salt is 480° C.-520° C., and the soaking time is 0.1 h-0.5 h.

[0038] According to a third aspect of the present disclosure, a structural member is provided, wherein the structural member is made of the microcrystalline glass provided by the first aspect of the present disclosure.

[0039] According to a fourth aspect of the present disclosure, an electronic device is provided, and the electronic device includes the structural component provided by the third aspect of the present disclosure.

[0040] The technical solution provided by the embodiment of the present disclosure may have the following beneficial effects: by adjusting the content of each component in the microcrystalline glass, the obtained microcrystalline glass has good impact resistance and fracture resistance, and the fracture toughness can be greater than 1.0 MPa·m 1 / 2 .

[0041] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0043] Figure 1 The present invention is a flow chart of a method for manufacturing glass-ceramics according to an exemplary embodiment.

[0044] Figure 2 is a differential scanning calorimetry curve of glass-ceramics according to an exemplary embodiment.

[0045] Figure 3 is a morphology diagram of microcrystalline glass after being etched by hydrofluoric acid according to an exemplary embodiment. DETAILED DESCRIPTION

[0046] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of devices and methods consistent with some aspects of the present invention as detailed in the appended claims.

[0047] Glass-ceramics is often used as a substitute for glass or ceramics because it has both the basic properties of glass and the polycrystalline characteristics of ceramics, and its performance indicators are better than similar glasses and ceramics. At present, the mechanical properties of glass-ceramics are still not ideal.

[0048] In view of this, the present disclosure provides a microcrystalline glass. By adjusting the content of each component in the microcrystalline glass, the obtained microcrystalline glass has good impact resistance and fracture resistance, especially the fracture toughness can be greater than 1.0 MPa·m 1 / 2.

[0049] An exemplary embodiment of the present disclosure provides a microcrystalline glass. In terms of mass percentage, the components of the microcrystalline glass include: SiO2: 60wt%-71wt%; Al2O3: 5wt%-13wt%; Li2O+Na2O+K2O: 9wt%-18wt%; ZrO2: 1.5wt%-6.5wt%; P2O5: 1.5wt%-5.5wt%; Y2O3: 0.1wt%-1.4wt%.

[0050] Glass-ceramic, also known as glass ceramics, is different from both ceramics and glass. The difference between glass-ceramic and ceramics is that the microcrystalline phase in the process of glass microcrystallization is a dense material produced by nucleation and crystal growth of the primary crystal phase from a single uniform glass phase or a phase-separated region. In addition to recrystallization or new crystal phases that appear through solid-phase reactions, most of the crystalline phases in ceramic materials are directly introduced through components during the preparation of ceramics. The difference between glass-ceramic and glass is that glass-ceramic is a complex phase material composed of microcrystalline phases and residual glass, while glass is a non-crystalline or amorphous body. Glass-ceramic has both the basic properties of glass and the polycrystalline characteristics of ceramics. It concentrates the characteristics of glass and ceramics, and its performance indicators are better than similar glass and ceramics. The role of each component in glass-ceramic is discussed independently below.

[0051] SiO2 forms an irregular continuous network with the structural unit of silicon-oxygen tetrahedron to form the microcrystalline glass skeleton, and stabilizes the various components in the microcrystalline glass. At the same time, SiO2 is also a necessary component for forming the microcrystalline phase in the microcrystalline glass. The higher the content of SiO2 (the content is the mass percentage of the component in the microcrystalline glass, the same below), the better the mechanical properties of the microcrystalline glass, but the viscosity of the microcrystalline glass melt will also increase, resulting in reduced solubility of the melt and difficulty in clarifying the melt. If the content of SiO2 is less than 60wt%, the crystallinity of the formed microcrystalline glass is low, and the desired microcrystalline phase cannot be obtained. Therefore, in the microcrystalline glass disclosed in the present invention, the mass percentage of SiO2 is limited to between 60wt% and 71wt%. In some examples, the mass percentage of SiO2 ranges from 60wt% to 70wt%. In some examples, the mass percentage of SiO2 ranges from 63wt% to 67wt%.

[0052] Al2O3 can form a glass network structure to form a microcrystalline glass skeleton. When combined with SiO2, it can substantially improve the mechanical properties of the glass and help stabilize the microcrystalline glass structure. At the same time, Al2O3 can improve the thermal conductivity of microcrystalline glass, and it is also a necessary component for forming a microcrystalline phase. If the content of Al2O3 is less than 5wt%, the desired optimal effect cannot be achieved. Since the melting point of Al2O3 is as high as 2054°C, if its content exceeds 13wt%, the solubility and devitrification resistance of the microcrystalline glass during melting will be adversely affected. Therefore, in the microcrystalline glass disclosed in the present invention, the mass percentage of Al2O3 is limited to between 5wt% and 13wt%. In some examples, the mass percentage of Al2O3 ranges from 5wt% to 12wt%. In some examples, the mass percentage of Al2O3 ranges from 7wt% to 10wt%.

[0053] Alkali metals Li2O, Na2O and K2O can play a good fluxing effect, reduce the difficulty of melting microcrystalline glass, and improve the low-temperature solubility of microcrystalline glass. At the same time, alkali metals can also promote the precipitation of microcrystalline phases in microcrystalline glass. In order to ensure that alkali metals achieve good effects, in the microcrystalline glass disclosed in the present invention, the sum of the mass percentages of Li2O, Na2O and K2O is limited to between 9wt% and 18wt%. In some examples, the sum of the mass percentages of Li2O, Na2O and K2O is in the range of 9wt% to 15wt%. In some examples, the sum of the mass percentages of Li2O, Na2O and K2O is in the range of 11wt% to 13wt%.

[0054] Among alkali metals, the role of Li2O can change based on the mass ratio of oxygen / silicon in the microcrystalline glass component. When the mass ratio of oxygen / silicon is relatively small, Li2O can promote bond breaking to make the microcrystalline glass easy to melt. As the melting proceeds, when the mass ratio of oxygen / silicon is relatively large, Li2O can reduce the thermal expansion coefficient of the microcrystalline glass, and at the same time, Li2O with a higher content can promote the formation of microcrystalline phases in the microcrystalline glass. Li2O is a necessary component for forming microcrystalline phases such as petalite, β-spodumene, β-eucryptite, and lithium silicate. If the content of Li2O is less than 8wt%, the melting of the microcrystalline glass is more difficult and the desired microcrystalline phase cannot be formed. If the content of Li2O is too high, it is easy to cause an increase in the average linear expansion coefficient of the microcrystalline glass, or the chemical durability of the microcrystalline glass is reduced, so that the stability of the microcrystalline glass is poor. Therefore, in the microcrystalline glass disclosed in the present invention, the range of the mass percentage of Li2O is limited to between 11.5wt% and 15.5wt%. In some examples, the mass percentage of Li2O ranges from 8 wt% to 16 wt%. In some examples, the mass percentage of Li2O ranges from 8 wt% to 12 wt%.

[0055] Na2O in alkali metals is an oxide outside the glass network. Sodium ions can reside in the holes of the glass structure network, thereby providing free oxygen to increase the oxygen / silicon ratio in the microcrystalline glass structure, causing bond breaking, reducing the viscosity of the microcrystalline glass melt, and making the microcrystalline glass easy to melt. At the same time, Na2O can also promote the precipitation of microcrystalline phases in microcrystalline glass. If the content of Na2O is less than 0.8wt%, the melting of microcrystalline glass is difficult, which is not conducive to industrial production. If the content of Na2O is too high, it is easy to cause the thermal stability, mechanical strength and chemical stability of microcrystalline glass to decrease, and it is easy to cause the thermal expansion coefficient of microcrystalline glass to increase. Therefore, in the microcrystalline glass disclosed in the present invention, the mass percentage of Na2O is limited to between 0.8wt% and 3.0wt%. In some examples, the mass percentage of Na2O ranges from 1wt% to 3wt%.

[0056] K2O in alkali metals can increase the difficulty of melting glass-ceramics at high temperatures, reduce the viscosity of the glass-ceramics melt, and thus increase the density of the glass-ceramics. If the content of K2O is too high, the crystallization of the glass-ceramics will be inhibited. Therefore, in the glass-ceramics of the present disclosure, the mass percentage of K2O is limited to between 0.2wt% and 1.0wt%. In some examples, the mass percentage of K2O is between 0.5wt% and 1.0wt%.

[0057] ZrO2 can improve the chemical stability and refractive index, hardness, elasticity and chemical stability of glass-ceramics, and reduce the ultraviolet transmittance and thermal expansion coefficient of glass-ceramics. At the same time, ZrO2 can form a microcrystalline phase in glass-ceramics, and can also reduce the energy required for the nucleation of the microcrystalline phase, so that nucleation can be carried out at a lower temperature, promote the formation of nuclei, and play the role of a nucleating agent. Since the melting point of ZrO2 is as high as 2680°C, if its content exceeds 6.5wt%, the solubility and devitrification resistance of glass-ceramics during melting will be adversely affected. Therefore, in the glass-ceramics disclosed in the present invention, the mass percentage of ZrO2 is limited to between 1.5wt% and 6.5wt%. In some examples, the mass percentage of ZrO2 ranges from 2wt% to 5wt%.

[0058] P2O5 helps to reduce the melting temperature and UV transmittance of the glass-ceramics melt, improve the dispersion coefficient and light transmittance of the glass-ceramics, and at the same time, P2O5 can form a microcrystalline phase in the glass-ceramics, and can also reduce the energy required for the generation of crystal nuclei, so that nucleation can be carried out at a lower temperature, promote the formation of crystal nuclei, and play the role of a nucleating agent. If the content of P2O5 is too high, it is easy to cause the devitrification resistance of the glass-ceramics to decrease. Therefore, in the glass-ceramics disclosed in the present invention, the mass percentage of P2O5 is limited to between 1.5wt% and 5.5wt%. In some examples, the mass percentage of P2O5 ranges from 2wt% to 5wt%. In some examples, the mass percentage of P2O5 ranges from 2wt% to 3wt%.

[0059] Since Y2O3 has a crystal structure with vacancies, ions of other components in the glass-ceramics can enter the vacancies in the Y2O3 crystals, which improves the compactness of the glass-ceramics structure, thereby improving the skeleton strength of the glass-ceramics and the bending strength of the glass-ceramics during use. However, as the content of Y2O3 increases, the thermal expansion coefficient of the glass-ceramics increases and the chemical stability decreases. Therefore, in the glass-ceramics of the present disclosure, the mass percentage of Y2O3 is limited to between 0.1wt% and 1.4wt%. In some examples, the mass percentage of Y2O3 ranges from 0.3wt% to 1.0wt%. In some examples, the mass percentage of Y2O3 ranges from 0.4wt% to 0.7wt%.

[0060] In some examples, by reasonably controlling the mass percentage ratio C1=SiO2 / Al2O3 in the range of 4.6-14.2, the microcrystalline glass can have good skeleton strength and the microcrystalline glass melt can have good formability. In some examples, the mass percentage ratio C1=SiO2 / Al2O3 can be in the range of 4.6-14.0.

[0061] In some examples, by reasonably controlling the mass percentage ratio C2=(SiO2+Al2O3) / Li2O in the range of 4.0-10.5, it is possible to ensure that the microcrystalline glass forms the desired microcrystalline phase, so that it has good mechanical strength and stability. In some examples, the mass percentage ratio C2=(SiO2+Al2O3) / Li2O can be in the range of 5.4-9.1.

[0062] Exemplarily, since glass-ceramics is a complex phase material including a glass phase and a microcrystalline phase, multiple microcrystalline phases may be included in glass-ceramics. Based on the mass proportion of multiple microcrystalline phases in a unit mass of glass-ceramics, the microcrystalline phases are divided into a first crystalline phase and a second crystalline phase, and the mass proportion of the first crystalline phase is greater than the mass proportion of the second crystalline phase. In a unit mass of glass-ceramics, the ratio of the total mass of the first crystalline phase and the second crystalline phase to the unit mass is greater than 90%, that is, in the glass-ceramics, the mass proportion of the microcrystalline phase is greater than 90%, and the mass proportion of the glass phase is less than 10%. For example, in 100kg of glass-ceramics, the total mass of the microcrystalline phase exceeds 90kg, and the total mass of the glass phase is less than 10kg.

[0063] In some embodiments, the first crystalline phase may include petalite (LiAlSi4O 10 ), β-spodumene (Li2O·Al2O3·4SiO2), β-eucryptite (β-LiAISiO4) or one or more thereof. Among them, petalite is a monoclinic crystal, Li is coordinated with O tetrahedron, and at the same time, it has a three-dimensional framework structure including a layered structure with folded Si2O5 layers connected by Li and Al tetrahedrons, which has a low thermal expansion coefficient. β-spodumene is a tetragonal crystal with a near-zero or even negative thermal expansion coefficient, and β-eucryptite is a quartz-like structure with a large thermal expansion coefficient and a low density. All three can make the microcrystalline glass have good thermal shock resistance and dimensional stability, and improve the service life of the microcrystalline glass. Exemplarily, in the unit mass of the microcrystalline glass, the mass of the first crystalline phase accounts for 50%-70%.

[0064] The second crystalline phase may include one or more of lithium disilicate (Li2Si2O5), lithium metasilicate (Li2SiO3), and zirconium oxide. The lithium disilicate crystal is a regular cubic structure, which can improve the mechanical properties of the microcrystalline glass. Lithium metasilicate has rhombic symmetry, and the (Si2O6) chains are parallel to the c-axis and connected together by lithium ions. In dilute hydrofluoric acid, lithium metasilicate crystals can be easily dissolved from microcrystalline glass. Zirconium dioxide crystals are body-centered cubic structures, which have good stability and high density, so that the microcrystalline glass has high hardness, strength, wear resistance and corrosion resistance. It can be understood that the second crystalline phase can also include other crystals with small contents, such as lithium phosphate, quartz, rutile, etc. Exemplarily, in the unit mass of microcrystalline glass, the mass of the second crystalline phase accounts for 30%-45%.

[0065] In some embodiments, the crystal grains of the microcrystalline phase may be spherical, that is, the crystal grains of the first crystal phase and the second crystal phase may be spherical, and the crystal grains of the spherical structure may make the microcrystalline glass have good hardness and strength. At the same time, the size of the spherical crystal grains ranges from 10nm to 70nm, so that the microcrystalline glass can be transparent or translucent in the visible light band, and its transmittance may be between 80% and 92%, so that the microcrystalline glass can be used as a replacement material for transparent glass. For example, the microcrystalline glass can be used as the back cover of an electronic device, the packaging cover of a display module, a camera structure, and the like.

[0066] In some embodiments, since the microcrystalline phase in the microcrystalline glass grows from the glass phase or the region where phase separation has occurred, the microcrystalline glass also includes an uncrystallized residual glass phase. The grains of the microcrystalline phase are closely arranged, and the glass phase exists between the grains of the microcrystalline phase, so that the grains can be interlocked with other adjacent grains in any direction through the glass phase. In this way, a microstructure with high fracture toughness is formed inside the microcrystalline glass. This microstructure can prevent the generation and expansion of cracks, so that the microcrystalline glass has good reliability. Exemplarily, the fracture toughness of the microcrystalline glass provided by the present disclosure can be greater than 1.0MPa·m 1 / 2 .

[0067] It is understandable that, due to the high content of hard components such as SiO2, Al2O3, and ZrO2 in the microcrystalline glass, and the presence of a variety of microcrystalline phases with high hardness inside the microcrystalline glass, the microcrystalline glass has a high hardness, thereby improving the friction and scratch resistance of the structural parts formed by the microcrystalline glass. Exemplarily, the Vickers hardness of the microcrystalline glass can be greater than 860HV50 / 10, that is, the microcrystalline glass material is kept under a test force of 50kg for 10s, and the hardness value is greater than 860HV.

[0068] In some embodiments, the glass-ceramics obtained by melting, forming, annealing, heat treating and ion exchanging the glass-ceramics formula provided by the present disclosure has a transparent or translucent appearance and good mechanical properties, and its fracture toughness can be greater than 1.0 MPa·m 1 / 2 , Vickers hardness is greater than 860HV50 / 10.

[0069] In an exemplary embodiment, the components of the microcrystalline glass include, in percentage by mass: SiO2: 60wt%-70wt%; Al2O3: 5wt%-12wt%; Li2O+Na2O+K2O: 9wt%-15wt%; ZrO2: 2wt%-5wt%; P2O5: 2wt%-5wt%; Y2O3: 0.1wt%-1.4wt%; B2O3: 0wt%-5wt%; TiO2: 0wt%-4wt%; MgO: 0wt%-2wt%; ZnO: 0wt%-2wt%; SrO: 0wt%-2wt%; clarifier: 0wt%-2wt%.

[0070] In this embodiment, the functions of components such as SiO2, Al2O3, Li2O, Na2O, K2O, ZrO2, P2O5, and Y2O3 have been described in detail in the above embodiments and will not be repeated here.

[0071] B2O3 may be included in glass-ceramics. When B2O3 is included, B2O3 is beneficial to reduce the melting temperature and viscosity of the glass-ceramics melt, and is beneficial to adjust the furnace atmosphere during the melting of the glass-ceramics. In addition, B2O3 also helps to achieve an interlocking crystal microstructure and improve the damage resistance of the glass-ceramics. However, if the content of B2O3 is too high, it is easy to cause the chemical durability and mechanical strength of the glass-ceramics to decrease. In an embodiment, the mass percentage of B2O3 contained in the glass-ceramics is generally greater than or equal to 0wt%, for example, between 0wt% and 5wt%. In some examples, the mass percentage of B2O3 may be between 0wt% and 1wt%.

[0072] TiO2 may be included in the microcrystalline glass. When TiO2 is included, TiO2 can improve the refractive index, chemical stability and fracture toughness of the microcrystalline glass, and increase the ability of the microcrystalline glass to absorb X-rays and ultraviolet rays. At the same time, TiO2 can also act as a nucleating agent to promote the formation of a crystalline phase. In an embodiment, the mass percentage of TiO2 contained in the microcrystalline glass is generally greater than or equal to 0wt%, for example, between 0wt% and 4wt%. In some examples, the mass percentage of TiO2 may be between 0wt% and 2wt%.

[0073] The glass-ceramics may contain MgO. When MgO is contained, MgO can improve the chemical stability and mechanical strength of the glass-ceramics, and can also enter the petalite crystal in the form of a partial solid solution. In an embodiment, the mass percentage of MgO contained in the glass-ceramics is generally greater than or equal to 0wt%, for example, between 0wt% and 2wt%.

[0074] Glass-ceramics may contain ZnO. When ZnO is contained, ZnO can reduce the thermal expansion coefficient of glass-ceramics and improve the chemical stability, thermal stability and refractive index of glass-ceramics. When glass-ceramics contain a large amount of free oxygen, ZnO can form oxygen-zinc tetrahedrons and enter the structural network of the glass, thereby improving the structural stability of the glass-ceramics. At the same time, ZnO can also enter the petalite crystal in the form of a partial solid solution. In an embodiment, the mass percentage of ZnO contained in the glass-ceramics is generally greater than or equal to 0wt%, for example, between 0wt% and 2wt%.

[0075] The glass-ceramics may contain SrO. In an embodiment, the mass percentage of SrO contained in the glass-ceramics is generally greater than or equal to 0 wt %, for example, between 0 wt % and 2 wt %.

[0076] The glass-ceramics may contain a clarifier. Since bubbles are easily generated in the glass-ceramics melt during the melting process of the glass-ceramics, the clarifier can be decomposed or vaporized during the melting process of the glass-ceramics to produce gas, thereby promoting the elimination of bubbles in the glass-ceramics melt and clarifying the glass-ceramics melt. In this way, it is possible to avoid bubbles from staying in the final glass-ceramics product, and avoid or reduce the impact of bubbles on the mechanical properties, light transmittance and product consistency of the glass-ceramics. Exemplarily, the clarifier may include one or more of Sb2O3, SnO2, SnO, and CeO2. In some embodiments, the mass percentage of the clarifier contained in the glass-ceramics is generally greater than or equal to 0wt%, for example, between 0wt% and 2wt%.

[0077] The present disclosure also provides a method for manufacturing microcrystalline glass, which can be used to manufacture the microcrystalline glass provided by one or more of the above embodiments of the present disclosure. Figure 1 As shown, Figure 1 FIG. 1 is a flow chart of a method for manufacturing glass-ceramics according to an exemplary embodiment. The method for manufacturing glass-ceramics may include the following steps:

[0078] Step S101, based on the mass percentage of each component, under a first preset condition, each component is melted to obtain a glass-ceramic melt;

[0079] Step S102, injecting the glass-ceramics melt into a mold at a preset temperature to form a precursor glass ingot;

[0080] Step S103, annealing the precursor glass ingot under the second preset condition to obtain a microcrystalline glass ingot;

[0081] Step S104: heat-treating the glass-ceramic ingot under a third preset condition.

[0082] In step S101, the components of the microcrystalline glass may include SiO2, Al2O3, Li2O, Na2O, K2O, ZrO2, P2O5, Y2O3, and may also include one or more of B2O3, TiO2, MgO, ZnO, SrO, and clarifiers. Based on the range of mass percentages of the components provided in the above embodiments, the raw materials are prepared so that the sum of the mass percentages of the components in the microcrystalline glass is equal to 100%. For example, the raw materials corresponding to SiO2 may include quartz sand, sandstone, quartzite, etc.; the raw materials corresponding to Al2O3 may directly use pure Al2O3, or wax stone; the raw materials corresponding to Li2O may include lithium carbonate; the raw materials corresponding to Na2O may include soda ash, sodium sulfate, etc., and the raw materials of other components may use commonly used chemical raw materials, as long as the sum of the mass percentages of the components is equal to 100%, and the present disclosure does not limit this.

[0083] The raw materials corresponding to each component are crushed, pulverized, screened, etc., and then mixed evenly, and each raw material component is put into a furnace and smelted under the first preset condition to obtain a microcrystalline glass melt. The first preset condition may be a condition suitable for melting the raw material components of the ratio, for example, it may include a smelting temperature and a smelting time. In some embodiments, the first preset condition may include: a smelting temperature between 1550°C and 1660°C, and a smelting time between 5h and 10h, that is, the raw material components are put into a furnace with a temperature between 1550°C and 1660°C, and within this temperature range, each raw material component is kept in a molten state and smelted for 5h-10h, thereby obtaining a microcrystalline glass melt.

[0084] In step S102, the smelted glass-ceramic melt is subjected to a molding process, and the molding process may include casting molding, pressing molding, drawing molding, calendering molding, and the like. In this embodiment, the glass-ceramic melt is injected into a mold at a preset temperature, and centrifugal casting or gravity casting is used to form the glass-ceramic melt into a precursor glass ingot corresponding to the shape of the mold, thereby completing the transition from molten state to solid state. Before the glass-ceramic melt is injected into the mold, the mold is preheated to a preset temperature, which is lower than the temperature of the glass-ceramic melt. The preset temperature may be the transition temperature at which the glass-ceramic melt changes from a molten state to a solid state. Exemplarily, based on the ratio of the raw materials of each component in the glass-ceramic melt provided in the present disclosure, the preset temperature may be any temperature between 750°C and 800°C. In some examples, the preset temperature may be between 780°C and 800°C.

[0085] In step S103, under the second preset condition, the formed precursor glass ingot is annealed. The annealing treatment can eliminate the stress in the precursor glass ingot, relax the structure of the precursor glass ingot, enhance the mobility of the atoms in the precursor glass ingot, and make the liquid phase separation in the precursor glass ingot. Liquid phase separation can affect the nucleation, crystal growth and crystal transformation process of microcrystalline glass. For example, in the case of liquid phase separation, the nucleating agent can be formed in the dispersed phase, or formed on the interface between the dispersed phase and the continuous phase to form densely arranged crystallites, each of which acts as a crystal nucleus. In other words, the microcrystalline glass ingot obtained after annealing can contain crystallites that can form grains.

[0086] The second preset condition may be a condition for annealing the precursor glass ingot having the composition ratio, for example, it may include a suitable annealing temperature and annealing time. In some embodiments, the second preset condition may include: the annealing temperature is between 500°C and 800°C, and the annealing time is between 5h and 12h, that is, the formed precursor glass ingot is placed in an annealing furnace with a temperature between 500°C and 800°C, and is kept warm for 5h to 12h at this temperature range and then cooled with the furnace to complete the annealing process and obtain a microcrystalline glass ingot. In some examples, the second preset condition may include: the annealing temperature is between 500°C and 650°C, and the annealing time is between 5h and 10h.

[0087] In step S104, since the microcrystalline phase in the microcrystalline glass ingot has not yet formed, the microcrystalline glass ingot is heat treated under the third preset condition, so that the desired microcrystalline phase is formed in the microcrystalline glass obtained after the heat treatment, and the shape and size of the grains meet the requirements of the required microstructure, so as to ensure that the obtained microcrystalline glass has good mechanical properties. The third preset condition can be a condition for heat treating the microcrystalline glass ingot having the composition ratio, for example, it can include a suitable heat treatment temperature and heat treatment time, and the heating rate when the microcrystalline glass ingot is heated from conventional room temperature (25°C) to the heat treatment temperature.

[0088] For example, a differential scanning calorimetry curve of the glass-ceramics may be measured to determine a suitable heat treatment temperature. Figure 2 is a differential scanning calorimetry curve of a glass-ceramic provided by an exemplary embodiment, with reference to Figure 2 As shown, the microcrystalline glass has an obvious exothermic peak at about 750.0°C, indicating that the microcrystalline glass can undergo good crystallization and crystal growth at this temperature. At the same time, since in the disclosed embodiment, the microcrystalline glass should be transparent or translucent, and the required grains are spherical grains with a size of 10nm-70nm, during heat treatment, controlling a lower heating rate, a lower heat treatment temperature, and a shorter heat treatment time is conducive to the formation of smaller spherical grains.

[0089] In some embodiments, the third preset condition may include: the heat treatment temperature is between 600°C and 750°C, and the heat treatment time is between 2h and 6h. The microcrystalline glass ingot is placed in a heat treatment furnace, and the temperature in the heat treatment furnace is controlled to rise from the conventional room temperature (25°C) to the heat treatment temperature, and the heating duration is 20h-22h. During the heating process of the heat treatment, the heat treatment furnace can be heated at a uniform rate of 0.48°C / min-0.61°C / min. As the temperature of the microcrystalline glass ingot increases and the time is extended, nucleation and growth of a metastable crystalline phase occur in the microcrystalline glass ingot. The metastable crystalline phase is not the microcrystalline phase of the composition point of the original glass on the phase diagram, but is in an intermediate state of the microcrystalline phase. It can be a crystallite or a transformation from a crystallite. As the temperature continues to rise, reaching the heat treatment temperature (600°C-750°C), the heat treatment temperature is maintained for 2h-6h. During this process, the metastable crystalline phase interacts, decomposes, dissolves, and undergoes isomorphous transformation. At the same time, crystals continue to precipitate in the microcrystalline glass ingot to form a stable final microcrystalline phase, thereby obtaining a microcrystalline glass with a stable microcrystalline phase. In some examples, the heat treatment temperature can be between 600°C-720°C.

[0090] It should be noted that in the above-mentioned first preset condition, the melting time of 5h-10h can be applicable to the melting of a small amount of microcrystalline glass raw materials (for example, the total mass of the component raw materials is between 2kg-5kg). At the same time, the annealing time in the above-mentioned second preset condition, the heat treatment time in the third preset condition, and the heating time during the heat treatment process are also applicable to the production of a small amount of microcrystalline glass raw materials. In industrial production, when a large melting furnace is used for melting, for example, when the total mass of the component raw materials of the microcrystalline glass exceeds 1 ton, the melting time can exceed 100h at a melting temperature of 1550℃-1660℃ to ensure that each component is fully melted, thereby ensuring that the microcrystalline glass can form the required microstructure and the performance meets the requirements. Since the size of the forming mold used in industrial production is larger, and the size of the precursor glass ingot and the microcrystalline glass ingot is also larger, the annealing time during the annealing treatment can exceed 20h, the heating time during the heat treatment process can exceed 80h, and the heat treatment time can exceed 15h.

[0091] In some possible implementations, after completing step S104 of the above embodiment, the method for manufacturing glass-ceramics further includes:

[0092] Step S105, cutting, grinding and polishing the heat-treated glass-ceramic ingot in sequence to obtain a glass-ceramic semi-finished product;

[0093] Step S106: Under the fourth preset condition, perform ion exchange treatment on the microcrystalline glass semi-finished product to obtain microcrystalline glass.

[0094] In order to make the final formed microcrystalline glass have good anti-destruction properties, it is necessary to perform ion exchange treatment on the microcrystalline glass ingot that has completed the heat treatment to form a stress compression layer on the surface of the microcrystalline glass. However, due to the large size of the mold used in the molding process in industrial production, the size of the microcrystalline glass ingot after the heat treatment is also large. If the cutting process is performed after the ion exchange treatment is completed, at least one side of the surface of the product obtained after cutting will not have a stress compression layer, making the product's anti-destruction property poor. Therefore, before the ion exchange treatment is performed, the microcrystalline glass ingot that has completed the heat treatment is cut. It is understandable that since the cutting surface of the cutting process and the molding surface that fits the mold may be relatively rough, in order not to affect the use of subsequent microcrystalline glass products, the semi-finished products after the cutting process are successively ground and polished to obtain microcrystalline glass semi-finished products of suitable size.

[0095] After obtaining a glass-ceramic semi-finished product of suitable size, the glass-ceramic semi-finished product is subjected to ion exchange treatment under the fourth preset condition to form a stress compression layer on the surface of the glass-ceramic semi-finished product, thereby obtaining a glass-ceramic with good anti-destruction properties. The ion exchange treatment is to immerse the glass-ceramic semi-finished product in an ion exchange solution, and the alkali metal ions (lithium ions, sodium ions) with a smaller radius on the surface of the glass-ceramic semi-finished product and in the material at a certain depth from the surface are replaced by alkali metal ions (sodium ions, potassium ions) with a larger radius, so as to form a stress compression layer on the surface of the glass-ceramic semi-finished product, so that the glass-ceramic has good anti-destruction properties. It can be understood that the fourth preset condition can be a condition suitable for alkali metal ion exchange, for example, it can include the temperature of the ion exchange solution, and the length of time that the glass-ceramic semi-finished product is continuously immersed in the ion exchange solution.

[0096] In some possible implementations, in step S106 in the above embodiment, when the semi-finished glass-ceramics product is subjected to ion exchange treatment, the semi-finished glass-ceramics product can be immersed in a first mixed salt in a molten state in sequence for a first treatment, and then immersed in a second mixed salt in a molten state for a second treatment. The first mixed salt and the second mixed salt are salts containing sodium ions and potassium ions, such as nitrates, nitrites, phosphates, sulfates, etc. In some examples, the first mixed salt and the second mixed salt both include NaNO3 and KNO3. In other examples, the first mixed salt and the second mixed salt both include NaNO3, KNO3, and LiNO3.

[0097] The essence of ion exchange treatment is to exchange the alkali metal ions with smaller radius in the surface of the semi-finished glass-ceramic product and the material at a certain depth from the surface with the alkali metal ions with larger radius in the mixed salt. +The content of Na + The ratio of the content of Na + Can fully integrate with the Li + For example, when the first mixed salt includes NaNO3 and KNO3, the mass ratio of NaNO3 to KNO3 is 4:6. When the semi-finished glass-ceramics product with a thickness of 0.5 mm to 1 mm undergoes the first treatment, the temperature of the molten first mixed salt is between 450°C and 550°C, and the semi-finished glass-ceramics product is continuously immersed in the molten first mixed salt at this temperature for 4h to 8h to complete the first treatment.

[0098] When the semi-finished glass-ceramic product undergoes the second treatment, most of the Li + Has been replaced by Na + , K with a larger radius in the second mixed salt + The content of Na + The ratio of the content of KNO3 can be in a larger range, that is, the content of KNO3 is higher, so that the obtained stress compression layer contains as many KNO3 with larger radius as possible. + , in order to improve the damage resistance of the obtained microcrystalline glass. Exemplarily, when the second mixed salt includes NaNO3 and KNO3, the mass ratio of NaNO3 to KNO3 is 3:7. When the microcrystalline glass semi-finished product with a thickness of 0.5mm-1mm undergoes the second treatment, the temperature of the molten second mixed salt is between 450℃-550℃, and the microcrystalline glass semi-finished product is continuously immersed in the molten second mixed salt at this temperature for 0.1h-0.5h to complete the second treatment.

[0099] In order to explain the technical solution of the present disclosure more clearly, the following are specific embodiments of the microcrystalline glass provided by the present disclosure, wherein the components, mass percentages and performance parameters of each embodiment are shown in Tables 1 and 2, and the samples tested in each embodiment and comparative example are polished and ion exchanged, and the size and shape of the samples tested in each embodiment and comparative example are the same. For example, the samples tested are all microcrystalline glass plates with a length*width*height of 165mm*70mm*0.6mm.

[0100] Table 1 Composition and performance parameters of glass-ceramics corresponding to Examples 1-8

[0101] category Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 <![CDATA[SiO2(wt%)]]> 70.00 67.00 65.00 63.50 70.00 61.00 60.00 62.80 <![CDATA[Al2O3(wt%)]]> 8.50 10.00 5.00 12.50 5.00 10.50 13.00 11.50 <![CDATA[Li2O(wt%)]]> 10.50 10.00 14.00 8.50 16.00 10.50 14.00 9.50 <![CDATA[Na2O(wt%)]]> 0.80 1.00 2.50 3.00 1.00 2.20 1.50 0.80 <![CDATA[K2O(wt%)]]> 0.20 1.00 1.00 1.00 0.50 0.80 0.30 1.00 <![CDATA[P2O5(wt%)]]> 2.50 3.00 3.00 2.50 1.50 3.80 3.00 4.80 <![CDATA[ZrO2(wt%)]]> 6.00 4.50 6.00 5.00 2.80 5.00 3.50 5.50 <![CDATA[Y2O3(wt%)]]> 0.50 0.70 0.50 1.00 0.20 1.40 1.20 0.20 <![CDATA[B2O3(wt%)]]> 0.50 0.30 / 0.50 0.30 1.50 0.50 1.20 <![CDATA[TiO2(wt%)]]> / 1.00 1.50 2.00 1.70 / 0.80 1.50 MgO (wt%) / 1.00 / / / 1.80 / 0.50 ZnO (wt%) / / 1.00 / / 0.70 1.50 / SrO(wt%) / / / / 0.50 / / 0.20 Clarifying agent (wt%) 0.50 0.50 0.50 0.50 0.50 0.80 0.70 0.50 Transmittance (%) 86 90 91 89 88 87 91 85 <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> 1.05 1.1 1.13 1.08 1.14 1.04 1.09 1.06 Drop ball height (cm) 150 165 155 145 160 155 160 155 Vickers hardness (HV) 872 863 867 870 865 876 868 871

[0102] Table 2 Components and performance parameters of glass-ceramics corresponding to Examples 9-14 and Comparative Examples 1-2

[0103]

[0104]

[0105] The transmittance is tested using an ultraviolet-visible spectrophotometer, and the measured wavelength range is the visible light band (350nm-780nm). Fracture toughness can characterize the ability of the microcrystalline glass plate to prevent crack propagation, that is, it is used to measure the resistance of microcrystalline glass to brittle fracture. The larger the value of fracture toughness, the stronger the toughness of the microcrystalline glass plate in resisting crack propagation, and the stronger the reliability of the microcrystalline glass plate. The fracture toughness of the microcrystalline glass provided by the present disclosure is greater than 1.0MPa·m 1 / 2 , glass-ceramics has good resistance to brittle fracture.

[0106] The ball drop height is used to characterize the impact resistance of the microcrystalline glass plate. The larger the value of the ball drop height, the better the impact resistance of the microcrystalline glass plate. When testing, the microcrystalline glass plate is placed on a rubber frame for fixing, and the microcrystalline glass plate is used as a horizontal plane. A steel ball with a mass of 32g is dropped on the microcrystalline glass plate from a certain height, and the maximum ball drop height that the microcrystalline glass plate can withstand without breaking is recorded as the "ball drop height" in Table 1 and Table 2. It should be noted that when conducting the impact resistance test, each embodiment is tested with 40cm as the starting height. When the microcrystalline glass plate does not break, the height of the latter test is 5cm greater than the height of the previous test. The ball drop height of the microcrystalline glass provided by the present disclosure is greater than or equal to 145cm, indicating that the microcrystalline glass has good impact resistance.

[0107] Vickers hardness is used to characterize the hardness of the microcrystalline glass plate, reflecting the friction resistance and scratch resistance of the microcrystalline glass plate. When testing, a square cone diamond indenter with a relative angle of 136° is pressed into the surface of the microcrystalline glass plate with a load of 50 kg. After holding for 10 seconds, the surface area of ​​the indentation pit is calculated. The fracture toughness of the microcrystalline glass provided by the present invention is greater than 860HV, and the microcrystalline glass has good hardness and wear resistance.

[0108] For example, the glass-ceramic plate corresponding to Example 2 is further measured, referring to Figure 3 , Figure 3 The morphology is obtained by scanning the microcrystalline glass plate corresponding to Example 2 with a dilute hydrofluoric acid after etching. The glass phase in the microcrystalline glass plate is etched by dilute hydrofluoric acid, and the microcrystalline phase is retained. Figure 3 The size of the grains in the microcrystalline glass plate is small, between 18nm-44nm, and the shapes of the grains include rods and spheres. Therefore, it has a higher light transmittance.

[0109] In an exemplary embodiment, the present disclosure further provides a structural part, which is made of the microcrystalline glass provided by the above embodiment of the present disclosure. Since microcrystalline glass has good light transmittance and mechanical properties, the structural parts made of microcrystalline glass can include, for example, battery covers, screen covers, camera baffles, camera lenses and other structural parts for 3C electronic devices, and can also include other structural parts that require good light transmittance and mechanical properties, such as optical parts in microscopes, etc. Structural parts made of microcrystalline glass can have good light transmittance and mechanical properties, so that the equipment or devices loaded with the structural parts have good reliability.

[0110] In an exemplary embodiment, the present disclosure further provides an electronic device, which may be a mobile phone, a tablet computer, a sports bracelet, a watch, a television, and other devices. The structural parts provided in the above embodiments of the present disclosure are assembled with the electronic device, and the structural parts can provide good performance for the electronic device. For example, when the electronic device is a mobile phone, and the structural parts are the device back shell and the screen cover, the screen cover has good light transmittance, and because the device back shell and the screen cover both have good mechanical properties, when the user accidentally drops the electronic device during use, the probability of cracking of the back shell and the screen cover can be avoided or reduced, and the probability of scratches on the back shell and the screen cover can be reduced, thereby improving the user experience.

[0111] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed in this disclosure. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.

[0112] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A glass-ceramic, characterized in that: In terms of mass percentage, the components of the microcrystalline glass include: SiO2: 60wt%-71wt%; Al2O3: 5wt%-13wt%; Li2O+Na2O+K2O: 9wt%-18wt%; ZrO2: 1.5wt%-6.5wt%; P2O5: 1.5wt%-5.5wt%; Y2O3: 0.1wt%-1.4wt%.

2. The glass-ceramic according to claim 1, characterized in that: The mass percentage ratio C1=SiO2 / Al2O3 ranges from 4.6 to 14.

2.

3. The glass-ceramic according to claim 1, characterized in that: In terms of mass percentage, in the microcrystalline glass, Li2O: 8wt%-16wt%; Na2O: 0.8wt%-3.0wt%; K2O: 0.2wt%-1.0wt%.

4. The glass-ceramic according to claim 3, characterized in that: The mass percentage ratio C2=(SiO2+Al2O3) / Li2O ranges from 4.0 to 10.

5.

5. The glass-ceramic according to claim 1, characterized in that: The microcrystalline glass comprises a microcrystalline phase, the microcrystalline phase comprises a first crystal phase and a second crystal phase, the first crystal phase comprises one or more of petalite, β-spodumene, and β-eucryptite, and the second crystal phase comprises one or more of lithium disilicate, lithium metasilicate, and zirconium oxide; In the unit mass of the microcrystalline glass, the ratio of the mass of the microcrystalline phase to the unit mass is greater than 90%.

6. The glass-ceramic according to claim 5, characterized in that: In a unit mass of the microcrystalline glass, the mass proportion of the first crystal phase is 50%-70%; the mass proportion of the second crystal phase is 30%-45%.

7. The glass-ceramic according to claim 5, characterized in that: The grains of the microcrystalline phase are spherical, and the size of the grains ranges from 10 nm to 70 nm.

8. The glass-ceramic according to claim 5, characterized in that: The microcrystalline glass also includes a glass phase, and every two adjacent grains of the microcrystalline phase are interlocked through the glass.

9. The glass-ceramic according to any one of claims 1 to 8, characterized in that: In terms of mass percentage, the components of the microcrystalline glass include: SiO2: 60wt%-70wt%; Al2O3: 5wt%-12wt%; Li2O+Na2O+K2O: 9wt%-15wt%; ZrO2: 2wt%-5wt%; P2O5: 2wt%-5wt%; Y2O3: 0.1 wt%-1.4wt%; B2O3: 0wt%-5wt%; TiO2: 0wt%-4wt%; MgO: 0wt%-2wt%; ZnO: 0wt%-2wt%; SrO: 0wt%-2wt%; Clarifying agent: 0wt%-2wt%.

10. The glass-ceramic according to claim 9, characterized in that: The clarifier includes one or more of Sb2O3, SnO2, SnO, and CeO2.

11. The glass-ceramic according to any one of claims 1 to 8, characterized in that: The Vickers hardness of the microcrystalline glass is greater than 860HV50 / 10; the fracture toughness of the microcrystalline glass is greater than 1.0MPa·m 1 / 2 .

12. A method for producing glass-ceramics, characterized in that: Used to prepare the microcrystalline glass according to any one of claims 1 to 11, the method for preparing the microcrystalline glass comprising: Based on the mass percentage of each component, under the first preset condition, each of the components is melted to obtain a glass-ceramic melt; Injecting the glass-ceramics melt into a mold at a preset temperature to form a precursor glass ingot; Under a second preset condition, annealing the precursor glass ingot to obtain a glass-ceramic ingot; Under a third preset condition, the glass-ceramic ingot is heat treated.

13. The method for producing glass-ceramics according to claim 12, characterized in that: The first preset conditions include: a smelting temperature of 1550°C-1660°C, a smelting time of 5h-10h; and / or, The preset temperature is 750°C-800°C; and / or, The second preset conditions include: annealing temperature of 500° C.-800° C., annealing time of 5 h-12 h; and / or, The third preset condition includes: the heat treatment temperature is 600° C.-750° C., and the heat treatment time is 2 h-6 h.

14. The method for producing glass-ceramics according to claim 12 or 13, characterized in that: The method for manufacturing the microcrystalline glass further includes: The glass-ceramics ingot that has completed the heat treatment is cut, ground and polished in sequence to obtain a glass-ceramics semi-finished product; Under a fourth preset condition, the microcrystalline glass semi-finished product is subjected to ion exchange treatment to obtain the microcrystalline glass.

15. The method for producing glass-ceramics according to claim 14, characterized in that: The semi-finished glass-ceramic product is subjected to ion exchange treatment, comprising: Immersing the semi-finished glass-ceramics product in a molten first mixed salt for a first treatment; Immersing the semi-finished glass-ceramics product that has undergone the first treatment in a molten second mixed salt for a second treatment; Wherein, the first mixed salt and the second mixed salt both include NaNO3 and KNO3.

16. The method for producing glass-ceramics according to claim 15, characterized in that: In the first mixed salt, the mass ratio of NaNO3 to KNO3 is 4:6; In the second mixed salt, the mass ratio of NaNO3 to KNO3 is 3:

7.

17. The method for producing glass-ceramics according to claim 15, characterized in that: The fourth preset condition corresponding to the first treatment includes: the temperature of the first mixed salt is 450°C-550°C, and the soaking time is 4h-8h; The fourth preset condition corresponding to the second treatment includes: the temperature of the second mixed salt is 480° C.-520° C., and the soaking time is 0.1 h-0.5 h.

18. A structural member, characterized in that: The structural member is made of the microcrystalline glass according to any one of claims 1-11.

19. An electronic device, characterized in that: The electronic device comprises the structural member according to claim 18.